Design Of Strategic Information System Blueprint With Enterprise Architecture Planning Method - Jakaria Rahmanto, Reza (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The rapid and dynamic development of information technology in today's digital era has a significant impact on organizations in managing information and data. This also applies to universities that need to optimize data and information management in order to improve service quality and organizational performance. Therefore, it is necessary to design an appropriate and integrated strategic information system, which is able to support the decision-making process effectively and efficiently, as well as integrate various functions and processes in various organizational units on campus. Enterprise is a set of organizations that have several general goals / principles and / or a baseline. Higher education is one of the enterprises engaged in education. The increasing need for data and information in business functions carried out by a university is one of the drivers of the use of information systems in universities. Therefore, in this study will be designed on 3 (three) architectural models, namely data architecture, architecture, applications and technology architectures using the Enterprise Architecture Planning (EAP) method.